Experimental candidosis on rat’s tongue - Junqueira, Juliana C.; Vasconcellos, Luana M. R.; Fernandes, Raquel G.; Chaves, Maria G. A. M.; Jorge, Antonio O. C. (Brazilian Dental Science, 2010)
The purpose of this study was to evaluate the development of candidosis in rat’s tongue after intraepithelial injections of Candida albicans. Fifty rats (Rattus norvegicus, Albinus, Wistar), originally negative for the Candida spp. received ten intraepithelial injections of C. albicans on the dorsal tongue. Groups of five animals were killed after 1, 2, 4, 6, 8, and 12 hours and 1, 2, 7, and 15 days after the injection. The rat’s tongues were surgically removed and then macroscopic and microscopic analyses were performed. The development of candidosis lesions was observed in all the rats studied. One hour after the injection, the development of germ tubes from the yeast cells could be observed. After 4 hours, Candida spp. pseudohyphae penetrated the epithelial cells with the formation of microabscesses. After 24 to 48 hours, the epithelial areas with pseudohyphae invasion presented desquamation, hyperplasia of the basal layer and discrete inflammation of the connective tissue. After seven days, few pseudohyphae could be observed. The epithelium presented acanthosis, hyperkeratosis and loss of filiform papillae. After 15 days, neither yeasts nor pseudohyphae were found. In some areas, the epithelium presented acanthosis and loss of filiform papillae. It can be concluded that the intraepithelial injection of Candida albicans on the dorsal rat tongue caused candidosis lesions in all the animals studied. C. albicans was present until seven days after the injections.